Iridium‐Catalyzed Enantioselective C(sp3)−H Borylation of Aminocyclopropanes. Issue 19 (14th March 2022) - Shi, Yongjia; Yang, Yuhuan; Xu, Senmiao
Abstract: Transition‐metal‐catalyzed regio‐ and stereo‐controllable C−H functionalization remains a formidable challenge in asymmetric catalysis. Herein, we disclose the first example of iridium‐catalyzed C(sp 3 )−H borylation of aminocyclopropanes by using simple imides as weakly coordinating directing groups under mild reaction conditions. The reaction proceeded via a six‐membered iridacycle, affording a vast range of chiral aminocyclopropyl boronates. The current method features a broad spectrum of functional groups (36 examples) and high enantioselectivities (up to 99 %). We also demonstrated the synthetic utility by a preparative scale C−H borylation, C−B bond transformations, and conversion of the directing group. Abstract : The first example of simple imide‐directed intermolecular enantioselective C(sp 3 )−H functionalization of aminocyclopropanes enabled by iridium catalysis has been developed. The reaction proceeds via six‐membered metallacycles. The method could tolerate a broad spectrum of functional groups, affording a vast array of chiral aminocyclopropanes (36 examples) with high enantioselectivities (up to 99 % ee ).